Pengaruh Pemberian Ekstrak Etanol Herba Anting-Anting (Acalypha indica) terhadap Ekspresi GLUT 2 pada Pankreas Tikus Diabetes - Toding, Ficanata Adhiguna; Islamiati , Utami; Wulandari, Ayu; Nugroho , Agung Endro; Widodo, Gunawan Pamudji; Patala , Recky (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Anting-anting herb (Acalypha indica L.) has been traditionally known for its antidiabetic properties. Its mechanism of action is presumed to involve the regeneration of damaged pancreatic β-cells; however, its effect on the expression of GLUT-2, a key glucose transporter in insulin secretion, remains to be further investigated. Objective: This study aimed to analyze the effect of ethanol extract of Anting-anting herb on GLUT-2 protein expression in pancreatic β-cells of Streptozotocin–Nicotinamide–induced diabetic rats. Methods: This laboratory experimental study used 25 male rats (Rattus norvegicus), randomly assigned into five groups: normal control, negative control (diabetes + 1% CMC), positive control (diabetes + glibenclamide 0.45 mg/kg BW), treatment 1 (diabetes + extract 100 mg/kg BW), and treatment 2 (diabetes + extract 200 mg/kg BW). Diabetes was induced intraperitoneally with Streptozotocin (50 mg/kg BW) and Nicotinamide (110 mg/kg BW). The treatments were administered orally for 14 days. GLUT-2 expression in pancreatic tissue was quantitatively analyzed using immunohistochemistry, and protein density was measured with ImageJ software. Data were analyzed using one-way ANOVA. Results: Phytochemical analysis revealed that the extract contained flavonoids, tannins, saponins, and steroids. The group treated with 200 mg/kg BW extract showed a significant increase in GLUT-2 protein density (11,608,400 molecules/µm²) compared with the negative control group (5,074,533 molecules/µm²) (p < 0.05). This value was even higher than that of the positive control (glibenclamide), which showed a density of 10,626,864 molecules/µm². Conclusion: Administration of ethanol extract of Anting-anting herb at a dose of 200 mg/kg BW significantly increased GLUT-2 expression in pancreatic β-cells of diabetic rats. This enhancement is strongly presumed to contribute to the antidiabetic mechanism of Anting-anting herb.